Reinterpretation Of Polygamy Verses: Analysis Study Of Maqashidi's Interpretation - Afriadi Putra; Safira Malia Hayati; Muhammad Yasir (QOF, 2021)
Maqashidi interpretation is able to provide new breakthroughs in the approach to understanding the Qur'an. The development of this study continues to be of interest. Maqashidi interpretation as a philosophy of interpretation will give a new spirit, not only in the product of the interpretation of the Qur'an, but also in the process of interpretation. The term maqashidi is not a new term because it was previously used in relation to shari'ah (maqashid as-Shari'ah). This is very much in accordance with the statement of the Qur'an which is pious kulli zaman wa makan. Maqashidi interpretation is generally used in interpreting legal verses. In this article, we discuss two focuses. First, how is the commentator's interpretation of the QS. An-Nisa'[4] verse 3, 128-130. Second, how is the application and analysis of maqashidi interpretation in QS. An-Nisa'[4] verses 128-130. The method that the author uses is the thematic method, which is discussing the verses based on a set theme. Aims to gain a focused understanding of the reinterpretation of polygamous verses with a review of maqashidi interpretations. This article is expected to be able to contribute to the Indonesian Muslim community in understanding the verses about the law contained in this polygamy and monogamy theme.